Cyber-physical production system approach for energy and resource efficient planning and operation of plating process chains - Leiden, Alexander; Herrmann, Christoph; Thiede, Sebastian (Journal of cleaner production, 2021)
Plating process chains are characterized by a high specific energy and resource demand as well as a high complexity due to dynamic interdependencies between and within processing steps. Planning and operating plating process chains should focus on aspects from cleaner production such as a high energy and resource efficiency, low impacts on the environment as well as on economic aspects. A high process transparency is required to meet these objectives and to evaluate the effects of improvement measures. An energy and resource flow simulation can support this by providing a fully parameterizable digital twin of the physical plating line. This simulation is integrated into a cyber-physical production system approach and connected to the IT environment of the plating company for the simulation of real scenarios. For the parameterization of the energy model, continuous and temporal measurements are combined systematically while the resource flow model is parameterized through information from the manufacturing IT systems. The successful implementation at a job plating company with an industrial acid zinc-nickel plating line indicated reachable electricity and resource savings of up to 10% in four scenarios. The electricity and plating metal demand was allocated to single carriers and products as basis for a product-based environmental and economic analysis. Especially in case of different carrier load levels, the energy and resource demand per product varies significant. The developed approach and its successful implementation emphasizes the need of a high process transparency for planning and operating plating process chains to accelerate the shift towards cleaner production. [Display omitted] •Planning and operation of plating process chain benefits from cyber-physical systems.•Cyber-physical systems approach enables integration of industrial data.•Product-specific allocation of energy and resource flows in plating process chains.•Energy and resource demand depends on carrier and product-specific parameters.